Study of the Potential and Development of Riam Sabada Natural Tourism Attractions in Sebatih Village Sengah Temila District Landak Regency West Kalimantan Province - Sesilia Indah Saptri; Slamet Rifanjani; Muflihati (Journal of Sylva Indonesiana, 2022)
Riam Sabada is one of the natural attractions in Landak Regency in the form of water flow over rocks with unspoiled nature and flora and fauna that potential to become tourist attractions. A potential assessment is carried out to find out whether the tourism object is the potential to be developed or not. Riam Sabada is one of the natural attractions in the Landak Regency, West Kalimantan Province. The study was conducted in October 2020 using observation and interview methods to 10 respondents selected by purposive sampling, which was determined intentionally by researchers. The respondent’s criteria were community leaders, had ever visited tourist objects, and had knowledge about Riam Sabada tourism. Data were analyzed using Microsoft Excel. Riam Sabada's ODTWA potential assessment results in a score of 460.27, which was included in the classification as possible enough to be developed. The unspoiled cascade area was surrounded by shady trees, large rocks, and flora and fauna such as civets, birds, melaban, and orchids. Riam Sabada's natural tourism development strategy was to implement policies that support an aggressive strategy (SO strategy) where the strategy was in a favorable position because it maximized the strengths and opportunities of the tourist attraction. However, to support development, it was necessary to build facilities and infrastructure and to study the carrying capacity of the Riam Sabada tourist attraction